Visual prognosis after standardized classification in patients with ocular trauma - Mariela Julia Curbelo Gómez; Maria Isabel González Mesa; Elvira Machado Héctor; María Adela Llull Tombo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Ocular traumas are a common cause of visual deficiency, mainly of monocular blindness. Objective: To compare the visual prognosis after the standardized classification of visual trauma. Methods: A descriptive study was carried out including 108 paediatric patients from the University Hospital "Paquito González Cueto" diagnosed with ocular trauma between January 2003 and December 2008. The programs used to process data were SPSS and Windows (11.0). The variables under study were: gender, age, circumstances of the trauma, causal agent, affected ocular area, initial degree of visual accuracy, diagnosis on hospital admission and standardized classification of ocular trauma. Results: There was a prevalence of males, with 85 patients aged more than 10 years old (43 children). The prevalent type of trauma was the closed trauma with 66 patients (66 %) and the most common diagnosis leading to their admission to hospital was hyphaemia (54 patients ). Conclusions: The correct application of the ocular trauma standardized classification allows damage classification as well as the patient's visual prognosis.